Primary retroperitoneal mucinous cystic neoplasm leading to multifocal invasive adenocarcinoma of the small and large intestine - Albina Joldoshova; Tatiana Belousova; Zhenjian Cai; Shahreen Billah (Elsevier, 2020)
Primary retroperitoneal mucinous cystic neoplasm (PRMCN) is extremely rare, and its etiology, pathogenesis, and prognosis remain unclear with histology being similar to ovarian or pancreatic counterparts. We herein report an unusual case of PRMCN with malignant transformation leading to multifocal invasive adenocarcinoma in the small and large bowel from our institution.The patient was a 23-year-old overweight woman presenting with fever, nausea, vomiting, abdominal pain, and 17 cm cystic lesion in the right mid abdomen which was exerting mass effect on the liver and right ureter. She underwent right hemicolectomy and en bloc resection of retroperitoneal mass with a subsequent pathology diagnosis of multifocal invasive moderately to poorly differentiated adenocarcinoma arising from a primary retroperitoneal mucinous cystic neoplasm with low and high grade dysplasia. The adenocarcinoma was identified in the serosa and muscularis propria of the small and large intestines. Immunohistochemically tumor cells were positive for CK7, pankeratin and MOC-31 with high Ki67 proliferative index, and negative for CK20, CDX-2, PAX-8, TTF-1, calretinin and WT1. Subsequent thorough oncologic, radiologic and tumor marker workup failed to identify any primary tumors in our patient with nineteen months surveillance after surgery being recurrence-free.There are no pathognomonic clinical or radiological findings for primary retroperitoneal mucinous cystic neoplasm, making the preoperative diagnosis challenging. Delay in diagnosis and treatment may lead to complications such as rupture, infection, and malignant transformation like in our case. Surgical resection and pathology report are crucial to facilitate accurate diagnosis and treatment.